Clinical features of pediatric mucormycosis: role of metagenomic next generation sequencing in diagnosis - Zhang, Yu; Wei, Erhu; Niu, Jiechao; Yan, Kunli; Zhang, Mengjiao; Yuan, Wenhua; Fang, Xiao; Jia, Peisheng (Frontiers in Cellular and Infection Microbiology, 2024)
Mucormycosis is an uncommon invasive fungal infection that has a high mortality rate in patients with severe underlying diseases, which leads to immunosuppression. Due to its rarity, determining the incidence and optimal treatment methods for mucormycosis in children is challenging. Metagenomic next-generation sequencing (mNGS) is a rapid, precise and sensitive method for pathogen detection, which helps in the early diagnosis and intervention of mucormycosis in children. In order to increase pediatricians' understanding of this disease, we conducted a study on the clinical features of mucormycosis in children and assessed the role of mNGS in its diagnosis. Methods: We retrospectively summarized the clinical data of 14 children with mucormycosis treated at the First Affiliated Hospital of Zhengzhou University from January 2020 to September 2023. Results: Of the 14 cases, 11 case of mucormycosis were classified as probable, and 3 cases were proven as mucormycosis. Most children (85.71%) had high-risk factors for mucormycosis. All 14 children had lung involvement, with 5 cases of extrapulmonary dissemination. Among the 14 cases, 4 cases underwent histopathological examination of mediastinum, lung tissue or kidney tissue, in which fungal pathogens were identified in 3 patients. Fungal hyphae was identified in 3 cases of mucormycosis, but only 1 case yielded a positive culture result. All patients underwent mNGS testing with samples from blood (8/14), bronchoalveolar lavage fluid (6/14), and tissue (1/14). mNGS detected fungi in all cases: 7 cases had Rhizomucor pusillus, 4 cases had Rhizopus oryzae, 3 cases had Rhizopus microsporus, 1 case had Lichtheimia ramosa, and 1 case had Rhizomucor miehei. Coinfections were found with Aspergillus in 3 cases, bacteria in 3 cases, and viruses in 5 cases.Children with mucormycosis commonly exhibit non-specific symptoms like fever and cough during the initial stages. Early diagnosis based on clinical symptoms and imaging is crucial in children suspected of having mucormycosis. mNGS, as a supplementary diagnostic method, offers greater sensitivity and shorter detection time compared to traditional mucormycosis culture or histopathological testing. Additionally, mNGS enables simultaneous detection of bacteria and viruses, facilitating timely and appropriate administration of antibiotics and thereby enhancing patient outcomes.